Factors Affecting Tax Aggressiveness - Liana Susanto (International Journal of Economic Research and Financial Accounting, 2022)
The Purpose of this research was to obtained an empirical evidence about the influence of Firm Characteristic and Corporate Governance towards Tax Aggressiveness. This study used manufacturing companies listed in Indonesian Stock Exchange from the year 2012 until 2015. The result of this study showed that firm characteristic which measured by leverage and firm size, and corporate governance which measured by controlling interest, proportion of independent boards, audit committee size have not significant influence toward tax aggressiveness. Meanwhile, firm characteristic which measured by profitability has significant influence toward tax aggressiveness.